(untitled) (Research, Society and Development, 2020)
The objective was to describe the characteristics of patients with chronic kidney disease undergoing hemodialysis, their facilities and difficulties in adhering to treatment. Descriptive study developed with the application of a form with 130 patients from a Ceará hemodialysis clinic, in 2017. Most patients were male (58%), 70% (91) were under 60 years old, 51 % (66) were married and 28% (36) were illiterate. Clinical-epidemiological data showed a greater impact of systemic arterial hypertension and associated diabetes mellitus (37%; 48), followed by only hypertension (28%; 37) and only diabetes (26%; 34). Facilities for adherence to treatment were described as the location of the clinic (40%) and the availability of transportation (12%). As difficulties, adaptation (34%), session time (24%) and access (91%) stood out. However, 80% never thought about abandoning treatment and 91.5% did not report negative thoughts about it, with 96.3% considering themselves happy, with faith and family support. The findings reinforce the patients adaptive capacity of patients to treatment and the need for professionals to strengthen the potential and difficulties of patients, to be worked on by the multidisciplinary team.